2001
DOI: 10.22358/jafs/67997/2001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soyabean meal, rapeseed meal and extruded field bean seeds on duodenal amino acids supply in sheep

Abstract: In the first of two experiments, four rumen cannulated wethers were used to determine the extent of rumen protein degradation in soyabean meal (SBM), rapeseed meal (RSM) and extruded field bean seeds (EFB), using the in sacco method. Rumen non-degradable N in SBM, RSM and EFB of total-N was 38, 29 and 48%, respectively. In the second experiment, four rams with cannulas in the duodenum were fed isoenergetic total mixed rations (TMR) containing similar amounts of protein truly digestible in the small intestine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In an earlier study (Urbaniak et al, 2001) in which this experimental diet was tested, it was found that Met and Lys concentration in total AA passing to the small intestine of sheep amounted to, 1.67 and 6.88%, respectively. Duodenal infusion of 2, 4 and 6 g/d of Met resulted in an increase of absorbable Met concentration which amounted to 3.15, 4.60 and 6.00%, respectively.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In an earlier study (Urbaniak et al, 2001) in which this experimental diet was tested, it was found that Met and Lys concentration in total AA passing to the small intestine of sheep amounted to, 1.67 and 6.88%, respectively. Duodenal infusion of 2, 4 and 6 g/d of Met resulted in an increase of absorbable Met concentration which amounted to 3.15, 4.60 and 6.00%, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…The composition of the concentrate, TMR chemical composition and nutritive value are given in Table 1. In an experiment carried out earlier (Urbaniak at al., 2001) the effect of the above mentioned TMR on AA profile and AA flow into the small intestine of sheep was determined. Daily amounts of DL-methionine were disolved in 240 ml of physiological salt solution, and infused into the duodenum via a peristaltic pomp for 6 h at a rate of 40 ml/h.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals were fed and milked twice daily at 7.00 and 16.00. In the last day of experimental period samples from morning and afternoon milkings were pooled according to yield and analysed for protein, fat and lactose contents by infrared analysis (Milkoscan 133B, Foss Electric, Denmark) and for amino acids using an automatic amino acid analyser (T-339, Microtechna, Czech Republic) according to methods given by Urbaniak et al (2001). Casein was determined according to the method given by Jurczak (1999).…”
Section: Methodsmentioning
confidence: 99%